Plainfin midshipman dissection, ejaculate, and sperm velocity data - Jessica Miller; C M Mazzoldi; M B Rasotto; Sigal Balshine (PANGAEA, 2019)
Plainfin midshipman fish dissection data including accessory gland mass data, data of percent sperm and seminal fluid in the ejaculate, and measurements of sperm velocity mixed with accessory gland node and lobule fluids.
Supplement to: Miller, J et al. (2019): Differential investment in male accessory glands: lessons from a marine fish with alternative reproductive tactics. Marine Biology, 166:37, https://doi.org/10.1007/s00227-019-3474-8